Masa Depan Pembelajaran Bahasa Arab Berbasis Artificial Intelligence: Tinjauan Literatur Kontemporer - Irfan Irfan (CV. SINAR HOWUHOWU, 2026)
The development of Artificial Intelligence (AI) has significantly transformed various aspects of human life, including education and language learning. In the context of Arabic language learning, AI offers numerous opportunities to enhance the effectiveness, flexibility, and personalization of the learning process. This article aims to examine the role of AI in Arabic language learning, identify its opportunities and challenges, and analyze its implications for the future of Arabic language education. This study employed a qualitative approach using a library research method. Data were collected from scholarly articles, books, and academic documents related to Artificial Intelligence and Arabic language learning published between 2020 and 2025. The data were analyzed through content analysis, involving data reduction, categorization, interpretation, and synthesis of findings from relevant literature. The results indicate that AI has been utilized to support the development of the four Arabic language skills, namely listening (mahārah al-istimā‘), speaking (mahārah al-kalām), reading (mahārah al-qirā’ah), and writing (mahārah al-kitābah), through technologies such as chatbots, speech recognition, text-to-speech systems, machine translation, and generative AI. The implementation of AI contributes to more personalized, adaptive, and accessible learning experiences while promoting learner autonomy. However, several challenges remain, including the linguistic complexity of Arabic, AI limitations in understanding cultural contexts, technological dependency, and concerns regarding academic integrity. Therefore, the integration of AI into Arabic language learning should be conducted carefully while maintaining the central role of teachers as facilitators of learning. This study concludes that AI has considerable potential to support the transformation of Arabic language education in the future, provided that its implementation is accompanied by the development of digital competence, AI literacy, and ethical technology use in educational settings.